Carex longipetiolata (Cyperaceae), a new sedge from Hainan, China - Wang, Qing-Long; Yang, Hu-Biao; Deng, Yun-Fei; Wang, Zhu-Nian; Liu, Guo-Dao (Phytotaxa, 2012)
Carex longipetiolata, a new species of Carex sect. Rhomboidales from Hainan, China, is described and illustrated. The new species is similar to C. saxicola, but differs in having wider leaves with the leaf base tapering into a long petiole, three shorter and sessile spikes, strictly female lateral spikes, and nutlets estipitate at base.